ANALISIS BAJA TIE ROD PADA PIER HEAD FALSEWORK DENGAN PENGGUNAAN BERULANG - Putri, Pratiwi Setyaning; Hastanto SM; Dicki Dian Purnama; Tommy Iduwin (Fakultas Teknik Universitas Krisnadwipayana, 2023)
Reinforcing steel is a very important material in construction, it cannot be avoided considering that reinforcing steel is one of the determining factors in the strength or failure of reinforced concrete construction [1]. The use of steel in construction is not only used as a reinforcing concrete in the structure but also as a falsework. So there is a possibility in the field that tie rod steel will be used repeatedly as falsework to save construction costs. This study aims to determine changes in steel behavior with repeated loading. The test is carried out by performing a tie rod steel tensile test according to SNI 07-0371-1998 repeatedly with a loading equal to the yield strength of steel. The results of the tensile test showed a difference in the value of stress and strain between the first and second tensile tests. Changes also occur in the ultimate tensile strength. Repeated use of steel tie rods as flasework can be carried out by loading no more than the yield strength.